2012
DOI: 10.1155/2012/759143
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Consumption of Platycodi Radix Ameliorates Obesity and Insulin Resistance via the Activation of AMPK Pathways

Abstract: This study was designed to evaluate the effects and mechanism of Platycodi radix, having white balloon flower (Platycodon grandiflorum for. albiflorum (Honda) H. Hara) on obesity and insulin resistance. The extracts of Platycodi radix with white balloon flower were tested in cultured cells and administered into mice on a high-fat diet. The Platycodi radix activated the AMPK/ACC phosphorylation in C2C12 myotubes and also suppressed adipocyte differentiation in 3T3-L1 cells. In experimental animal, it suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
(28 reference statements)
1
17
0
Order By: Relevance
“…ACC and FAS are key enzymes directly involved in fatty acid synthesis during lipogenesis and are known to be regulated by the AMPK signaling pathway. In agreement with our results, previous studies have shown that components or extractions of PG can mediate expression or activation of FAS, ACC, and other genes involved in the AMPK pathway to affect lipid metabolism in adipose and liver tissue in metabolic disease models [20,21,27]. Here, we demonstrated for the first time that dietary intervention by whole PG is efficient to improve hepatic steatosis via affecting expression of key enzymes.…”
Section: Discussionsupporting
confidence: 92%
“…ACC and FAS are key enzymes directly involved in fatty acid synthesis during lipogenesis and are known to be regulated by the AMPK signaling pathway. In agreement with our results, previous studies have shown that components or extractions of PG can mediate expression or activation of FAS, ACC, and other genes involved in the AMPK pathway to affect lipid metabolism in adipose and liver tissue in metabolic disease models [20,21,27]. Here, we demonstrated for the first time that dietary intervention by whole PG is efficient to improve hepatic steatosis via affecting expression of key enzymes.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, Radix platycodi is also one of the key compounds of TH as it improves obesity and insulin resistance in obese mice via the activation of AMPK/ACC pathways and reduces of adipocyte differentiation [84]. We also obtained the results that TH may modulate fatty acid metabolizing proteins/genes involved in obesity and hepatic injury, particularly via the AMPK pathway.…”
Section: Discussionmentioning
confidence: 81%
“…Among various ingredients of TH, Schisandrae fructus, Herba ephedrae, and Radix platycodi have reported to exhibit protective effects against hyperlipidemia and hepatoteatosis [80][81][82][83][84]. Moreover, Radix platycodi is also one of the key compounds of TH as it improves obesity and insulin resistance in obese mice via the activation of AMPK/ACC pathways and reduces of adipocyte differentiation [84].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that platycodin D regulates adipogenesis via the Wnt/β-catenin (27) and AMPK-dependent signaling pathways (28). In another study, it ameliorated obesity and insulin resistance in obese mice via the activation of the AMPK/ACC pathways, and also reduced adipocyte differentiation (29). It has been reported that Platycodon grandiflorum extract ameliorated obesity in mice fed a high fiber diet and increased glucose uptake in L6 muscle cells by modifying adipokines, which indicates clinical benefits of platycodon as a supplement to treat obesity and diabetes (30).…”
Section: Discussionmentioning
confidence: 94%